Cell towers and the ambient population: a spatial analysis of disaggregated property crime - Johnson, Patrick (European journal on criminal policy and research, 2021)
As a crime rate denominator, the ambient population has seen very limited use in a multivariate context. The current study employs a new measure of this population, constructed using cell tower location data from OpenCellID, to compare residential and ambient population-based crime rates. The chosen study area is Vancouver, BC, but the conclusions generalize to other administrations and the OpenCellID data have global coverage so the implications are applicable elsewhere. Five disaggregated property crime types are examined at the dissemination area level. Findings demonstrate striking differences in the spatial patterns of crime rates constructed using these two different measures of the population at risk. Multivariate results from spatial error models also highlight the substantial impact that the use of a theoretically informed crime rate denominator can have on pseudo R2 values, variable retention, and trends in significant relationships. Implications for theory testing and policy are discussed. In particular, the results suggest that policies designed around residential-based crime rates risk having no effect, or even of increasing crime.